Ordinance No. 126: An Ordinance Relating to the Carrying of Concealed Weapons, THE VIRGINIA ENTERPRISE, Feb. 9, 1912, at 12 (Virginia, Minnesota). - (:unkn) unknown (General Publisher, 1912)
No person shall go armed with a dirk, dagger, sword, pistol, revolver, air-gun, stiletto, metallic knuckles, pocket billie, sand bag, skull cracker, sling shot, razor or other offensive and dangerous weapon or instrument concealed upon his person, within the limits of the City of Virginia. Provided this ordinance shall not apply to public officers of the City of Virginia when on duty, nor to any person whose occupation or business may seem to require the carrying of weapons for protection, and who shall have obtained from the Mayor of said city a license so to do.
--
Keywords: CARRY - CONCEALED